THE ROLE OF WOMEN'S WRITING CONSCIOUSNESS IN FORMING THE INTELLECTUAL POTENTIAL OF THE NEW UZBEKISTAN (Universal International Scientific Journal, 2026)
The article examines the concept of female authorial consciousness as a dynamic category changing in the context of the socio-political renewal of Uzbekistan. The relationship between the literary subjectivity of a woman and her contribution to the scientific and intellectual development of the country is studied. The author analyzes the evolution of the female "I" from an object of depiction to an active creative subject in the context of the Third Renaissance.
Keywords: authorial consciousness, women's creativity, New Uzbekistan, intellectual potential, comparative literary studies, typology, evolution, cultural context, Third Renaissance, gender subjectivity.